Multi-scale modeling of mechanical behavior of cured woven textile composites accounting for the influence of yarn angle variation. (September 2019) - Liang, Biao; Zhang, Weizhao; Fenner, Joel S.; Gao, Jiaying; Shi, Yi; Zeng, Danielle; Su, Xuming; Liu, Wing K.; Cao, Jian
Abstract: In most current works related to the structure analysis of cured woven composites, the influence of yarn angle variation on the local material properties is neglected. In this paper, its influence was studied, and an integrated preforming-performance simulation model, accounting for the influence of yarn angle variation, was proposed. The multi-scale modeling approach was adopted to predict the material properties of cured woven composites with different yarn angles. The results were compared with experiments to validate its effectiveness. In the integrated preforming-performance simulation model, non-orthogonal constitutive law was used in the preforming simulation to compute yarn orientations and yarn angle distribution. To demonstrate the capabilities of the integrated simulation model, simulations were conducted and compared with experiments. The results show that the proposed simulation model has more accurate prediction than the simulation model without considering the influence of yarn angle, and the impact of yarn angle shouldn't be neglected.